Реплантация конечностей - Датиашвили Рамаз Отарович (Передовой опыт, 1991)
Экземпляры: КХ (20111003) / Инвентарный номер: 984682 / Цена: 2.60 / Сис.шифр: 54.58 / Авт.знак: Д 20 / ГРНТИ: 76 / ББК: 54.582.8